2006
DOI: 10.1111/j.1083-6101.2004.tb00282.x
|View full text |Cite
|
Sign up to set email alerts
|

How Attitude Toward the Web Site Influences Consumer Brand Choice and Confidence While Shopping Online

Abstract: As more and more consumers spend more money on the Internet, traditional retailers and manufacturers as well as entrepreneurial dot‐coms are jousting to explore and shape this new business opportunity. Their long‐term survival and profitability may be determined by how well the Web site helps form and sustain positive attitudes toward the site and, eventually, toward the product or the company. The purpose of this study is two‐fold: (1) to examine if and how attitude toward the Web site (Ast) affects consumer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 26 publications
0
14
0
5
Order By: Relevance
“…The concept of attitude and its hierarchical effects have also been transposed and explored in the Internet context (Chen and Wells, 1999;Stevenson et al, 2000;Lee et al, 2004). In terms of Internet advertising, previous studies have stressed the potential of the sponsored ad as it is a less invasive form of communication.…”
Section: The Central Role Of Attitudementioning
confidence: 99%
“…The concept of attitude and its hierarchical effects have also been transposed and explored in the Internet context (Chen and Wells, 1999;Stevenson et al, 2000;Lee et al, 2004). In terms of Internet advertising, previous studies have stressed the potential of the sponsored ad as it is a less invasive form of communication.…”
Section: The Central Role Of Attitudementioning
confidence: 99%
“…Outros têm se interessado em verificar características diversas de websites que se relacionam com atitudes de compras online (Shergill & Chen, 2003). Lee, Hong e Lee (2004), por sua vez, verificaram que atitudes favoráveis de estudantes universitários em relação a websites predizem o comportamento de consumo de marcas e a fidelidade à marca e que o conhecimento do produto moderou essa relação.…”
Section: Websites: Pesquisas Prévias Na Psicologiaunclassified
“…Theories point out that attitude towards the website can directly influence brand attitude in a manner analogous to attitude towards the advertisement (Chen et al ., ; Chen & Wells, ). Studies have found that attitude towards the website could predict consumer brand choices (Lee et al ., ) and attitude towards the brands advertised on the site (Bellman & Rossiter, ). Moreover, as interacting with a website creates an interactive experience, components that are not related to brands but crucial to web‐based interactivity make an additional contribution to attitude towards the website and generate a greater impact on consumers' responses than traditional advertisements (Karson & Fisher, , b).…”
Section: Literature Reviewmentioning
confidence: 99%